A arte e o pôr-se-em-obra da verdade na filosofia de Martin Heidegger - Siqueira, Ana Carla de Abreu (2014)
The main aim of this dissertation is to state that the truth is set in artworks. We use the perspective of Martin Heidegger as the base of our argument. Firstly, we display how Heidegger interprets aesthetical themes and their key concepts. After questioning art as mimesis, Heidegger inspects the course of inputting art in the horizon of aesthetics. His investigation lengthens the Nietzsche’s thought that while maintaining the aesthetic debate around the subjects who contemplate the art subject; one would not have meditated on the artwork itself. Then, we follow promoting a review of the conference The Origin of the Work of Art’s guiding concepts, when the philosopher analyzes the origin as a founding leap. By situating artworks in a site where they are considered further than ordinary things and utensils, it gives them the character of carrying within themselves the time of a historical people. Finally, we analyze the deconstruction of truth as suitability, interpreting it as unconcealment, the recognition consisted in the removal of an entity’s veiling. The truth would be conquered in the struggle between World and Earth, that which is manifested against that which is hidden. This tension is effected in the artwork, be it figurative, architectural or poetic. Without the intention of drafting a new artistic theory or placing it in an aesthetic, Heidegger believed that art is essentially a originator and foundation of the truth.